2021
DOI: 10.1016/j.joca.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of structure and function changes of sensory nervous system in intervertebral disc-related low back pain

Abstract: Low back pain (LBP) is a common musculoskeletal symptom, which can be developed in multiple clinical diseases. It is widely recognized that intervertebral disc (IVD) degeneration (IVDD) is one of the leading causes of LBP. However, the pathogenesis of IVD-related LBP is still controversial, and the treatment means are also insufficient to date. In recent decades, the role of structure and function changes of sensory nervous system in the induction and the maintenance of LBP is drawing more and more attention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 129 publications
0
49
0
Order By: Relevance
“…The normal structure of IVD is avascular that is poorly innervated, with the most nerve fibers existing in the outer 1/3 of AF [ 12 ]. In the past few decades, the role and changes of nerve systems during the progression of IVDD have attracted growing attention among researches [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The normal structure of IVD is avascular that is poorly innervated, with the most nerve fibers existing in the outer 1/3 of AF [ 12 ]. In the past few decades, the role and changes of nerve systems during the progression of IVDD have attracted growing attention among researches [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…IVDD, a common but complex process, is frequently associated with LBP. Evidence showed that the pro-inflammatory microenvironment played a critical role in IVDD progression and LBP development ( Zhang et al, 2021a ; Lyu et al, 2021 ). Multiple anti-cytokine agents and signaling pathway inhibitors were investigated to ameliorate IVD inflammation and delay IVDD in preclinical and clinical studies ( Risbud et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main reasons associated with IVDD include nutritional, environmental, and genetic factors [ 11 , 12 ]. These factors lead to changes in cell morphology, inflammation, an increase in senescence cells, apoptosis, and autophagy [ 13 , 14 , 15 , 16 , 17 , 18 ]. IVDD is characterized by a loss of NP cells (more rounded chondrocyte-like cells) and their replacement by cells with a fibroblast-like phenotype [ 19 ].…”
Section: Introductionmentioning
confidence: 99%